FACIAL ZONES AND COMPLEXES OF TABULATE-CORALS - HRYTSENKO, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
Abundance of tabulate corals into Silurian-Lower Devonian of Volyn-Podillya region sequences allows to use it remains to facial analyse.